Production, Competition Indices, and Nutritive Values of Setaria splendida, Centrosema pubescens, and Clitoria ternatea in Mixed Cropping Systems in Peatland - A Ali; L Abdullah; P D.M.H Karti; M A Chozin; D A Astuti (Media Peternakan, 2013)
This research was conducted to evaluate production, different competition indices and nutritive value of Setaria splendida, Centrosema pubescens, and Clitoria ternatea in monoculture and mix cropping system on peat soil land. The experiment was set up in a randomized complete block design with five treatments and three replications. The five treatments were:  S. splendida sole cropping (SS), C. pubescens sole cropping (CP), C. ternatea sole cropping (CT), S. splendida and C. pubescens mix cropping (SS/CP) and S. splendida/C. ternatea mix cropping (SS/CT). The DM yield of S. splendida in mixed cropping with C. pubescens increased 43.4% and in mix cropping with C. ternatea increased 15.7% compared to sole S. splendida. The value of land equivalent ratio of SS/CP (LERSS/CP) was >1. The LERSS/CT value was <1.  The crowding coefficient value of S. splendida (KSS) was higher than KCP and KCT. The total value of KSS/CP and KSS/CT were >1. The competition ratio (CR) values of S. splendida in both mix cropping were >1. The agressivity (A) values of S. splendida in both mix cropping were positive. The crude protein, NDF and ADF content of forage were not affected by mix cropping system. In conclusion, mix cropping in peatland do not affect productivity and nutritive value of S. splendida,  C. pubescens, and C. ternatea. S. splendida is more effective in exploiting environmental resources when intercropped with C. pubescens compared to C. ternatea on peatland.